Red Fruit Carotenoids as SARS-CoV-2 RdRp Inhibitors: An in Silico Study - Agus Ananto; Anjar Purba Asmara (Jurnal Biologi Tropis, 2026)
Understanding the molecular interactions between natural bioactive compounds and viral proteins is essential for exploring the therapeutic potential of tropical plant resources. This study aimed to investigate the molecular interactions between carotenoids from Pandanus conoideus Lam. and the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) using an in silico molecular docking approach. The crystal structure of RdRp (PDB ID: 7D4F) was retrieved from the Protein Data Bank and prepared using YASARA-Structure. The docking protocol was validated through native ligand redocking, yielding a root mean square deviation (RMSD) of 1.8285 Å, confirming the reliability of the docking procedure. Eight carotenoid compounds were evaluated and compared with Remdesivir as the reference ligand. Although Capsanthin 3,6-epoxide exhibited the most favorable predicted binding energy (−6.755 kcal/mol), Cryptocapsin demonstrated the most biologically relevant interaction profile by forming hydrogen bonds with the catalytic residues Ser759 and Asp760, supported by hydrophobic and van der Waals interactions. The remaining carotenoids also interacted with the RdRp active site through distinct binding patterns. These findings provide molecular insights into carotenoid–RdRp interactions and highlight Pandanus conoideus as a valuable tropical source of bioactive compounds for early-stage antiviral research. Further molecular dynamics simulations, ADMET profiling, and experimental validation are required to confirm the biological significance of these computational predictions.